EFFECT OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) ON THE PATIENTS WITH CHRONIC LOW BACK PAIN : SYSTEMATIC REVIEW - Wulansari, Denta; Marzuqi, Imam; Nur Arniati, Layli; Surya Saputra, Bryan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The ailment known as low back pain (LBP) is quite common and intricate. It is frequently advised that people receive pharmaceutical therapy in order to reduce the burden of LBP on their everyday life Aims : This systematic review is to review the effect and efficacy of transcutaneous electrical nerve stimulation in the treatment of chronic low back pain. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, ScienceDirect and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 240 articles, whereas the results of our search on SAGEPUB brought up 1.683 articles, our search on SCIENCE DIRECT brought up 1.647 articles. The results of the search conducted for the last year of 2014 yielded a total 124 articles for PubMed, 610 articles for SAGEPUB and 429 articles for SCIENCE DIRECT. In the end, we compiled a total of 7 papers, 4 of which came from PubMed, 1 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included seven research that met the criteria. Conclusion: In summary, although the use of transcutaneous electrical nerve stimulation (TENS) still controversial in medical to treat low back pain, the studies mostly showed that TENS can reduce the pain of chronic low back pain (CLBP), and also can decreased the function of the back.